2012
DOI: 10.1109/tsmcc.2012.2198055
|View full text |Cite
|
Sign up to set email alerts
|

Toward Intelligent Security Robots: A Survey

Abstract: Abstract-In this paper, a survey is being conducted on the investigation of a four-class taxonomy related to security robots that appeared over the past three decades. The survey emphasizes on state-of-the-art mobile technologies that have been developed for crime-fighting robots, capable of crafting critical situations with confrontation strategies. Throughout this investigation, 60 projects are being examined with respect to faculties and sensor apparatus being used. A statistical analysis, which is carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…CT is suitable when the number of targets does not considerably exceed the number of robots and there might be the need of close observation of some specific targets, e.g. using security robots [102].…”
Section: A Cooperative Tracking (Ct)mentioning
confidence: 99%
“…CT is suitable when the number of targets does not considerably exceed the number of robots and there might be the need of close observation of some specific targets, e.g. using security robots [102].…”
Section: A Cooperative Tracking (Ct)mentioning
confidence: 99%
“…(cx n , 2y n ); 0 y n 0.5 B (x n ,y n ) = where 0 < c < 0.5 (1) (1+c (x n -1), 2y n -1); 0.5 < y n 1…”
Section: Along Xaxis Along Yaxismentioning
confidence: 99%
“…There has been a recent growth in the use of autonomous patrol & surveillance robots in civil and military applications [1,2]. Besides mobile, patrol robots are also commercially available today, for e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Multirobot systems are expected to undertake imperative roles in a wide variety of fields such as urban search and rescue (USAR) [1,2], agricultural field operations [3], security patrols [4,5], environmental monitoring [6], and industrial procedures [7]. Studies have shown that multi-robot systems have advantage over single-robot systems by offering more reliability, redundancy, and time efficiency when the nature of the tasks is inherently distributed [8].…”
Section: Introductionmentioning
confidence: 99%